Clinical usefulness of gated technetium-99m sestamibi myocardial perfusion single-photon emission computed tomography with phase analysis for the management of patients with isolated ventricular noncompaction. Issue 4 (April 2015) - Takahashi, Naoto; Sato, Naoki; Takagi, Koji; Omote, Toshiya; Kikuchi, Arifumi; Hanaoka, Daisuke; Yamamoto, Eisei; Ishikawa, Masahiro; Amitani, Kenichi; Kumita, Shinichiro; Shimizu, Wataru
Abstract: Gated Tc-99m sestamibi myocardial perfusion single-photon emission computed tomography (GMPS) with phase analysis provides information on myocardial perfusion, left ventricular (LV) function, and LV dyssynchrony. We present a case of isolated left ventricular noncompaction (IVNC) cardiomyopathy in which GMPS with phase analysis proved to be beneficial and reliable to monitor the long-term response to cardiac resynchronization therapy with defibrillator (CRT-D). The patient was an 84-year-old man with shortness of breath on minimal exertion (New York Heart Association class III) who had severe drug-refractory heart failure with hypotension and ventricular tachycardia. He was diagnosed with IVNC using echocardiography. At baseline, GMPS with phase analysis revealed a reduced ejection fraction (EF, 21%), large perfusion defects in the inferior and inferolateral walls, and severe LV dyssynchrony [histogram bandwidth (HBW) 120°]. Combination therapy with CRT-D and a titrated beta-blocker was initiated to induce LV reverse remodeling and reduce LV dyssynchrony. Two years after CRT-D implantation, GMPS with phase analysis showed marked improvement in LV function and LV dyssynchrony (EF 28%, HBW 36°). This case demonstrates that GMPS with phase analysis is an important and useful modality to evaluate LV function and LV dyssynchrony in IVNC patients undergoing CRT-D. <Learning objective: We experienced a rare case of heart failure with isolated left ventricular noncompaction (IVNC) treated with cardiac resynchronization therapy with defibrillator (CRT-D). We demonstrate that gated Tc-99m myocardial perfusion SPECT (GMPS) with phase analysis can simultaneously evaluate myocardial perfusion and left ventricular dyssynchrony to assess the indication and efficacy of CRT-D. This case demonstrates that GMPS with phase analysis is useful to monitor IVNC patients before and after CRT-D.>